2012
DOI: 10.4187/respcare.01660
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Obstructive Sleep Apnea in Patients With and Without Cardiovascular-Related Diseases

Abstract: Patients with any of the cardiovascular-related diseases are at a higher risk of having moderate to severe OSA without significant increase in daytime sleepiness. Therefore, we suggest that patients with any of the cardiovascular-related diseases should be screened for OSA, even if they are asymptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…A number of studies examined the association between sleep efficiency and arterial blood pressure, often reporting conflicting results [ 19 , 20 ]. Good sleep efficiency, defined as sleep efficiency >90%, was less frequently observed among OSAS patients with cardiovascular disease (OR 0.45 (0.22–0.91)) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies examined the association between sleep efficiency and arterial blood pressure, often reporting conflicting results [ 19 , 20 ]. Good sleep efficiency, defined as sleep efficiency >90%, was less frequently observed among OSAS patients with cardiovascular disease (OR 0.45 (0.22–0.91)) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study [ 22 ] that compared systolic arterial pressure and heart rate, nocturnal dipping between subjects with low and high sleep efficiency demonstrated that the group with low sleep efficiency presented a blunted dip of nocturnal systolic arterial pressure (10 ± 1 versus 14 ± 1%, p =0.04) and heart rate (12 ± 3 versus 21 ± 3%, p =0.03) compared with the high sleep efficiency group. Additionally, the low sleep efficiency group had higher mean nocturnal heart rate (63 ± 2 versus 55 ± 2 beats/min, p =0.02) [ 21 ]. In women, poor sleep quality has been associated with resistance to hypertensive treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simon et al . [ 30 ] in a cohort of 190 subjects tried to see whether any of the cardiovascular diseases correlated with the severity of OSA. They found that patients with any risk factor were noticed to have more severe OSA with an odds ratio 3.24.…”
Section: Discussionmentioning
confidence: 99%
“…7 Simon et al recently suggested that cardiovascular-related disease may indicate a higher risk for sleep apnea and that elderly patients with cardiovascular disease should be screened for sleep apnea. 8 Interventions for OSA include weight loss, altered sleeping positioning, and CPAP. 9 Elderly patients who use CPAP for OSA have increased alertness; improved neurobehavioral outcomes in cognitive processing, memory, and executive function; and decreased sleep disruption.…”
Section: Introductionmentioning
confidence: 99%